Examining Physical and Cognitive Function in Chronic Low Back Pain Through the Use of a Multisystem Resilience Framework. Issue 5 (21st October 2022) - Bartley, Emily J; Makhoul, Melissa; Palit, Shreela; Robinson, Michael E; Fillingim, Roger B
Abstract: Objectives: Chronic pain results in significant impairment in older adults, yet some individuals maintain adaptive functioning. Limited research has considered the role of positive resources in promoting resilience among older adults. Likewise, these factors have largely been examined independently. We aimed to identify resilience domains based on biopsychosocial factors and explore whether resilience phenotypes vary across sleep disturbance, fatigue, and cognitive function. Methods: Sixty adults (ages ≥60 years) with chronic low back pain completed measures of psychological, health, and social functioning. On the basis of previously published analyses, principal-components analysis was conducted to create composite domains for these measures, followed by cluster analysis to identify phenotypes. Results: Four profiles emerged: Cluster 1, with high levels of psychosocial and health-related functioning; Cluster 2, with high health-related functioning and low psychosocial functioning; Cluster 3, with high psychosocial functioning and poorer health; and Cluster 4, with low levels of functioning across all domains. Significant differences across cluster membership emerged for sleep disturbance ( ηp 2 = 0.29), fatigue ( ηp 2 = 0.29), and cognitive abilities ( ηp 2 = 0.47). Individuals with the highest levels of resilience demonstrated more optimal outcomes in sleep and fatigue ( P values ≤0.001) than did individuals with a less resilient phenotype. Furthermore, the High-Resilience group (Cluster 1) and the High Psychosocial / Low Health group (Cluster 3) had lower cognitive impairment than did the High Health / Low Psychosocial group (Cluster 2) and the Low-Resilience group (Cluster 4) ( P values ≤0.009). Conclusions: A higher array of protective resources could buffer against the negative sequelae associated with chronic low back pain. These exploratory findings support the multidimensional nature of resilience and suggest that targeting resilience from a multisystem perspective might help to optimize interventions for older adults with chronic pain.